PELATIHAN CARA PENGEPAKAN DAN CARA PEMASARAN PRODUK HANDY CRAFT ACCESSORIES DI PPTQ AR ROHMAH DESA CODO KECAMATAN WAJAK KABUPATEN MALANG - Ana Faizatus Sholichah; Mila Suraya (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2022)
Codo Village, Wajak District, Malang Regency is a village with a predominantly Muslim population, so that in this village there are many Islamic boarding schools that have been established. There are many opportunities to carry out community development programs through young men and women at the Islamic boarding school in Codo Village. One of the trainings that has the potential to be carried out is Training on Making Handy Craft Accessories and how to pack and market them. Through this training the students/students in the pesantren can explore their potential and develop their creativity in the field of Handy Craft. The steps taken are as follows: (1) direct observation to the Islamic boarding school; (2) Analyze the results of the observations; (3) The 2nd observation is carried out to describe the work program to be carried out at the pesantren; (4) carry out training; and (5) Evaluation of program implementation. The training was held in one place, namely at the PPTQ AR ROHMAH in Codo Village. The participants were very enthusiastic in participating in the training. They train pretty well and earnestly. Many of the participants were skilled at the end of the training.